MICROSOFT TEAMS AND ONLINE DISTANCE LEARNING: AN ACADEMIC PERSPECTIVE - Noor Haty Nor Azam; Ts. Nur Elimtiaz Abidin; Gladys Sebi Entigar (Journal of Islamic, Social, Economics and Development, 2021)
Online Distance Learning (ODL) is a current trend in the education system in Malaysia. Most educational institutions in Malaysia shift to online distance learning in response to the Ministry of Higher Education in Malaysia's current requirements. Both public and private educational institutions take part to involve in this new approach. Universiti Teknologi MARA Cawangan Melaka also takes part in delivering Online Distance Learning (ODL) to the students. The lecturer must serve this purpose to be more flexible in teaching and achieve organizational objectives and accommodate the students’ need in acquiring knowledge. Many platforms have been identified and tested by the lecturers such as Microsoft Teams, Google Classroom, and Learning Management Systems provided in the educational institution. From the exploration of several platforms, the lecturers can identify which of the platform can meet the requirement and needs of both students and lecturers. Besides, the survey was conducted regarding students’ readiness and perception towards Online Learning. Hence, the objective of this paper is to discuss an overview of Microsoft Teams and Online Distance Learning and Online Learning from the lecturer’s perspective. Moreover, this paper will be focused on the benefits of Microsoft Teams on ODL among students at UiTM Cawangan Melaka.